2006
DOI: 10.1111/j.1600-0765.2006.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Dense fimbrial meshwork enhances Porphyromonas gingivalis adhesiveness: a scanning electron microscopic study

Abstract: The results indicate that P. gingivalis adhesiveness is prominently enhanced by the dense fimbrial meshwork. Thus, the virulence of P. gingivalis is increased by the presence of rich fimbriae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Fimbriae directly increase P. gingivalis adhesiveness by promoting inter-bacterial aggregation [34] [35] As CSE increases fimbrial density, we determined whether CSE promotes bacterial auto-aggregation. P. gingivalis , grown in GAM or CSE, was harvested by centrifugation and suspended in sterile PBS at O.D.…”
Section: Methodsmentioning
confidence: 99%
“…Fimbriae directly increase P. gingivalis adhesiveness by promoting inter-bacterial aggregation [34] [35] As CSE increases fimbrial density, we determined whether CSE promotes bacterial auto-aggregation. P. gingivalis , grown in GAM or CSE, was harvested by centrifugation and suspended in sterile PBS at O.D.…”
Section: Methodsmentioning
confidence: 99%
“…Electron microscopy studies have revealed that FimA constitutes a prominent surface molecule of P. gingivalis (11), perhaps being the first molecule of this pathogen coming into contact with epithelial cells. In this regard, oral gingival epithelial cells provide a physical barrier against invading bacteria and play an important role in the host's innate defense (1).…”
Section: Discussionmentioning
confidence: 99%